1995
DOI: 10.1021/jf00058a007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative caffeoylquinic acid derivatives in the roots of burdock (Arctium lappa L.).

Abstract: Five antioxidative caffeoylquinic acid derivatives were isolated from the roots of burdock (Arctium lappa L.), an edible plant in Japan. Their structures were established as 1-0-,5-O-dicaffeoylquinic acid (1), l-0-,5-0-dicaffeoyl-3-0-succinylquinic acid (2), l-0-,5-0-dicaffeoyl-4-0-succinylquinic acid (3), l-0-,5-0-dicaffeoyl-3-0-,4-0-disuccinylquinic acid (4), and 1-0-,3-0-,5-0-tricaffeoyl-4-0-succinylquinic acid (5) on the basis of chemical and spectral (NMR, MS) evidence. The antioxidant activities were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
101
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 10 publications
(12 reference statements)
3
101
0
3
Order By: Relevance
“…Edible burdock includes chlorogenic acid, caffeic acid and caffeic acid derivatives as the phenolic compounds (Chen et al, 2004;Maruta et al, 1995). As phenolic compounds express anti-allergic and anti-inflammatory effects (Kimura and Okuda, 1987;Shimoda et al, 2006;Song et al, 2008), they may be the active compounds in the burdock methanol extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Edible burdock includes chlorogenic acid, caffeic acid and caffeic acid derivatives as the phenolic compounds (Chen et al, 2004;Maruta et al, 1995). As phenolic compounds express anti-allergic and anti-inflammatory effects (Kimura and Okuda, 1987;Shimoda et al, 2006;Song et al, 2008), they may be the active compounds in the burdock methanol extracts.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16] The antifungal activity of compounds 1, 2, 6-10 against Cladosporium cladosporioides and C. sphaerospermum was evaluated by direct bioautography on a TLC plate. 17,18 Only compound 1 exhibited moderate activity (MIC of 100 μg), when compared with the standard nystatin (1.0 μg).…”
Section: Resultsmentioning
confidence: 99%
“…We indicated that a smaller amount of alloxan administration to the acatalasemic mouse developed diabetes than that to normal ones [3], and then deduced that acatalasemic animals promoted diabetes faster and more frequently than normal ones [4]. The root of burdock, Artium lappa, is taken as a vegetable in Japan and contains high amounts of dietary fibers as well as polyphenols such as chlorogenic and caffeic acids [5] [6]. However, there are few preparations to take considerable amounts of the roots as foods.…”
Section: Introductionmentioning
confidence: 98%